Forest regeneration on Hinewai Reserve, New Zealand: An interview with Hugh Wilson - Wilson, H.; McDonald, Tein; Lamb, D. (Wiley-Blackwell Publishing Ltd, 2017)
© 2017 Ecological Society of Australia and John Wiley & Sons Australia, Ltd In 1986 the paths of two men crossed – one who had started a Trust fund to purchase land for conservation and the other who was looking for land to test his hunches about forest regeneration. The two joined forces and the subsequent 30 years saw a growth in both the Trust and the forest such that today it is a 1,500 ha regrowth rainforest with a network of indefatigable supporters.